Selenium and Vitamin E Concentrations in Miranda Jennies and Foals (Equus asinus) in Northeast Portugal - Miguel Quaresma; Carmen Marín; Daniel Bacellar; Miguel Nóvoa; Francisco Javier Navas; Amy McLean (Animals, 2021)
The increase in donkeys treated by practitioners in recent years has led to an increased interest in finding more information on basic biochemical preliminary reference values. The aims of this study were to measure Se and Vit E levels in plasma from Miranda jennies peripartum and postpartum and in their foals to compare blood profiles of the jenny and foal related to the overall foal’s health. Twenty-two healthy peripartum and postpartum Miranda donkeys were sampled (12 jennies and 10 foals) in the northeast of Portugal (Atenor and Paradela) from May to November, 2018. Amounts of selenium in soil were significantly correlated (0.97) to concentrations of selenium in jennies (42.412 μg/L in Atenor and 9.612 μg/L in Paradela) and foals (19.378 μg/L in Atenor and 6.430 μg/L in Paradela). Selenium levels were lower in foals than adults and in males than females. Vitamin E was associated with overall foal health. Foals with a mean vitamin E of 3.585–5.307 mg/L showed signs of weakness, but carpal flexural deformities were observed when the average vitamin E was 11.520 mg/L. Low vitamin E levels (5.307 mg/L) in jennies were related to foal mortality. Diets, location, parity, and age affect blood profiles of jennies and, ultimately, foal health.